Prediksi Hasil Panen Padi Tahun 2023 menggunakan Metode Regresi Linier di Kabupaten Indramayu - Diyanti yanti; Martanto; Agus Bahtiar (Jurnal Informatika Terpadu, 2023)
Indramayu Regency has the West Java region's largest harvested land area and the most rice production. The size of harvested land in the Indramayu Regency area has also increased from year to year. In 2019 Indramayu Regency had a land area of 215,731 Ha; then, land acquisition increased the size of land in Indramayu Regency in 2020 it increased to 226, 626 Ha, and in 2021 it increased again to 227,051 Ha. Certain factors play an essential role in raising standards and increasing productivity. These factors are planting area, harvested area, rainfall, and crop failure, where these factors cannot be predicted. This research will discuss the application of the Linear Regression method, namely the method used to examine the relationship between a tertiary variable and two or more secondary variables. Based on predictions using the python programming language, the rice harvest in 2023 is 1510403 tons/GKP, with MAE, MSE, RMSE, and R2-Score values. The system displays MAE (Mean Absolute Error) values: 5449.45, MSE (Mean Squared Error) values: 72325540.80, RMSE (Roots Mean Squared Error): 8504.44, and R2-Score: 0.93 with predictions that 2023 will experience a decrease from the previous year.